Humite- and scapolite-bearing assemblages in marbles and calcsilicates of Dronning Maud Land, Antarctica:New data for Gondwana reconstructions - Piazolo, S.; Markl, G. (Journal of Metamorphic Geology, 1999)
This study investigates marbles and calcsilicates in Central Dronning Maud Land (CDML), East Antarctica. The paleogeographic positioning of CDML as part of Gondwana is still unclear; however, rock types, mineral assemblages, textures and P-T conditions observed in this study are remarkably similar to the Kerala Khondalite Belt in India. The CDML marbles and calcsilicates experienced a Pan-African granulite facies metamorphism at c. 570 Ma and an amphibolite facies retrogression at c. 520 Ma. The highest grade assemblage in marbles is forsterite+spinel+calcite+dolomite, in calcsilicates the assemblages are diopside+spinel, diopside+garnet, scapolite+wollastonite+clinopyroxene±quartz, scapolite±anorthite±calcite±clinopyroxene±wollastonite. These assemblages constrain the peak metamorphic conditions to 830±20°C, 6.8±0.5 kbar and X(CO(2))>0.46. During retrogression, highly fluoric humite-group minerals (humite, clinohumite, chondrodite) replaced forsterite, and garnet rims formed at the expense of scapolite during reactions with wollastonite, calcite or clinopyroxene but without involvement of anorthite. Metamorphic conditions were about 650 °C, 4.5±0.7 kbar, 0.2<X(CO(2))(fluid)<0.36, and the co-existence of garnet, clinopyroxene, wollastonite and quartz constrains f(O2) to FMQ-1.5 log units. Mineral textures indicate a very limited influx of H 2 O-rich fluid during amphibolite facies retrogression and point to significant variations of fluid composition in mm-sized areas of the rock. Gypsum was observed in two samples; it probably replaced metamorphic anhydrite which appears to have formed under amphibolite facies conditions. The observed extensive anorogenic magmatism (anorthosites, A-type granitoids) and the character of metamorphism between 610 and 510 Ma suggest that the crustal thermal structure was characterized by a long-lived (50-100 Ma) rise of the crustal geotherm probably caused by magmatic underplating.